Isolation of Bacillus spp. Strains from soil biocenoses and their screening for phytase activity - Astrakhanov, M.; Baltin, K.; Bizhanova, B.; Maksutova, K.; Khassenov, B. (Eurasian Journal of Applied Biotechnology, 2026)
Phosphorus is a component of phosphates, nucleic acids, necessary for the synthesis of proteins, phospholipids, metabolic enzymes, and intracellular buffers. Therefore, all feeds must contain phosphorus in digestible form. In plant-based feeds, about 60-90% of phosphorus is found in the form of phytinic acid and its salts - phytates, which have anti-nutritive properties, which affects the maintenance of animals with a simple stomach: poultry, pigs, fish. Phytate, which is a phosphorus-containing waste from poultry farms, pig farms, and pond farms, negatively impacts the environmental situation. Fitases, which are myo-inositol phosphohydrolases, catalyze the hydrolysis of phytin acid to monophosphate and intermediate myo-inositol phosphate, which allows for the simultaneous solution of three problems: eliminating the need for feed phosphorus, reducing the anti-nutritional value of feed, and improving the ecological situation near poultry farms, farms, and pond facilities. From soil samples collected from the territories of the Akmola, Turkestan, Kyzylorda, and Zhambyl regions, 10 isolates of microorganisms belonging to the species Cytobacter oceaanisediminis, Peribacillus simplex, Bacillus mojavensis, Bacillus cereus, Bacillus pumilus, Bacillus thuringiensis, Bacillus megaterium, Bacillus subtilis, Bacillus paralicheniformis were isolated. Screening showed that 9 of these strains are capable of hydrolyzing phytinic acid, indicating their phytase activity. Of these, Bacillus mojavensis SH1 and Bacillus megaterium 1POL strains were selected as the most active strains for research. The study of biochemical properties showed that the phytase from B. mojavensis SH1 is active in the temperature range of 30-37°C and pH 8.0, while the phytase from B. megaterium 1POL is active at 60°C and pH 4.0-7.0. Phytase activity was 0.34 U/ml for the B. mojavensis SH1 and B. megaterium 1POL strains. The obtained results indicate the prospects of using B. mojavensis SH1 and B. megaterium 1POL strains as bacterial phytase producers.